Children's Manners towards Parents in the Digital Era: A Study of Qs. Al-Isra' Verses 23-24 and Its Implications for Generation Z Family Relations - Safrida Ramadhania; Nasrulloh Nasrulloh (Tilawah: Journal of Al-Qur'an Studies, 2026)
The phenomenon of weakening children's manners towards parents among Generation Z in the digital age indicates a communication crisis, emotional distance, and changing interaction patterns within Muslim families. This study aims to analyze the meaning of Quranic ethics contained in Qs. Al-Isra' verses 23-24 and contextualize them with the social realities of Generation Z. Using qualitative methods based on literature studies and a thematic interpretation approach, this study examines the interpretations of classical and contemporary commentators and integrates them with the findings of empirical studies and field observations. The analysis shows that the core values ​​of birrul walidain, including ihsan (doing good deeds), the prohibition of harsh language (uff), qawlan kariman (noble speech), and compassionate humility, are facing serious challenges due to a digital lifestyle filled with instantaneousness, individualism, and screen-based communication. Phenomena such as neglecting communication, harsh verbal behavior, and the degradation of digital politeness reflect a disorientation of values ​​in parent-child relationships. The results of this study emphasize the need to revitalize Quranic ethics through family education, digital mentoring, and the internalization of spiritual values ​​in online and offline communication patterns. This study offers a framework for Quranic digital ethics as a strategy for reconstructing Muslim family relationships to maintain harmony, empathy, and compassion amidst the increasingly dominant digitalization.